(untitled) (Scientific journal of the Fergana State University, 2024)
In the article, the pedagogical foundations of future German language teachers’ formation of the ability to work with students’ verbal errors are studied. The forms of correcting verbal mistakes made by students, such as teacher-student, student-student, teacher-student-teacher, were analyzed. Methods of correcting verbal errors are systematized.